Measuring justice: notes on fish, Foucault, and the law - S. Mailloux (Law Text Culture, 1997)
My paper can be described in several ways. It is an illustration of something I call rhetorical hermeneutics: the use of rhetoric to practice theory by doing history (Mailloux 1989). It is also part of a larger project on "The Ancients and the Postmodem": an argument that much poststructuralist thought in law, critical theory, and other human sciences can be usefully understood as a contemporary reception of classical Greek rhetoric and philosophy (Shankman 1994, Mailloux 1995, Zuckert 1996). In the following remarks, I suggest how Michel Foucault's genealogical work is both derived from and employed in a reading of Plato and Aristotle on justice. Here I use rhetoric (tracing the trope of measurement) to practice a bit of legal theory (concerning neopragmatism) by doing some reception history (about the law). Specifically, I look at Foucault's genealogy of the will to truth in ancient Greek philosophy and legal practices and relate it to Stanley Fish's theoretical claims about the distinctive purpose of law as a particular social practice aiming to disengage from history to establish formal procedures for legal validity.